2018
DOI: 10.1002/ecs2.2231
|View full text |Cite|
|
Sign up to set email alerts
|

Hurricane disturbance and forest dynamics in east Caribbean mangroves

Abstract: Despite low plant diversity and structural simplicity, mangroves offer various ecosystem services to local human communities, including sheltering coastal social‐ecological systems from high‐energy storm damage. The expected increasing intensity of hurricanes due to climate change raises questions concerning the capacity of mangroves to resist and recover from such disturbances. Herein, this study contributes to a better understanding of (1) the relation between storm intensity and damage to mangrove vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 47 publications
(115 reference statements)
1
64
1
6
Order By: Relevance
“…Baldwin et al 2001). Avicennia spp ., however, have repeatedly been found to be of the most resistant species to hurricane disturbance (Woodroffe and Grime 1999; Daniel Imbert 2018), so its failure to regrow in this study is contradictory. It’s possible that because all sites in this study were fringe systems of low A. germinans density (Branoff and Martinuzzi 2018), recovery following the storm was made more difficult by stressful and unsuitable habitat.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Baldwin et al 2001). Avicennia spp ., however, have repeatedly been found to be of the most resistant species to hurricane disturbance (Woodroffe and Grime 1999; Daniel Imbert 2018), so its failure to regrow in this study is contradictory. It’s possible that because all sites in this study were fringe systems of low A. germinans density (Branoff and Martinuzzi 2018), recovery following the storm was made more difficult by stressful and unsuitable habitat.…”
Section: Discussionmentioning
confidence: 57%
“…Still another study of the same storm in the Dominican Republic found L. racemosa to be the least affected, and A. germinans (Avicennia germinans) the most (Sherman et al 2001). Other studies for other storms in other locations have found variations in species susceptibilities (Wadsworth 1959; Smith et al 1994; Daniel Imbert 2018). This conflict might be explained by differences in habitat and hydro-geomorphology, both of which have also been found to play a role in storm related tree mortality and forest recovery (Sherman et al 2001; Smith III et al 2009; Daniel Imbert 2018).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations